2016
DOI: 10.1111/ans.13853
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy for early oral cancers: Westmead Hospital experience

Abstract: SLNB for early OCSCC is technically feasible in an Australian setting. It has a high NPV and can potentially identify at-risk lymphatic basins outside the traditional selective neck dissection levels even in well-lateralized lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Two authors individually collected data from included articles in forms commensurate with each other. Diagnostic accuracy, represented by DOR, summary receiver operating characteristic (SROC) curve, and area under the curve (AUC), was calculated 1,5,11–102 . DOR was calculated as (true positive [TP]/false positive [FP])/(false negative [FN]/true negative [TN]) to assess diagnostic accuracy with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…Two authors individually collected data from included articles in forms commensurate with each other. Diagnostic accuracy, represented by DOR, summary receiver operating characteristic (SROC) curve, and area under the curve (AUC), was calculated 1,5,11–102 . DOR was calculated as (true positive [TP]/false positive [FP])/(false negative [FN]/true negative [TN]) to assess diagnostic accuracy with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…A total of seven studies with 457 patients were included in the meta-analysis 16,26,27,33,34,37,47 . The eligibility of the articles was determined by the data provided in each article.…”
Section: Resultsmentioning
confidence: 99%
“…The mean number of SLNs detected by lymphoscintigraphy or single-photon emission CT with CT (SPECT/CT) was 2 to 3 in N0 early oral cancer [5, 10, 12], and the most common location of SLNs was level I to III using RI [29]. Regarding the location of SLNs detected by CTL, Honda et al [2] reported SLNs at level I to III; in our study, SLNs were at level I to II and in the sublingual region.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, 70 to 80% of patients with early oral cancer who underwent ND may experience complications such as facial nerve paralysis or shoulder dysfunction. Therefore, the concept of the sentinel lymph node (SLN), which is the first lymph node to receive drainage from a primary tumor, has recently been applied in detecting early lymph node metastasis in oral cancer patients [112], and SLN biopsy (SLNB) has been demonstrated to be less invasive than prophylactic ND. Although SLN detection using radioisotope (RI) tracers is commonly performed [4, 5, 814], RI cannot be used in certain institutions due to restrictions regarding the handling of radioactive material [2].…”
Section: Introductionmentioning
confidence: 99%